Selfie- liking and its relationship to some personality Traits among a sample of university students - Ahmed, Bushra Othman (Al-Adab Journal, 2022)
The aim of the present study is to identify the level of selfie- liking among students of Baghdad University and recognize the differences between males and females, and the correlation between selfie- liking and the personality traits. A random sample of (135) University students has been selected (64males and 61 females), selfie- liking (6 items) and narcissism (8items) scales responding according to 5-Likert scale ranging from (strongly agree- strongly disagree). And Loneliness (6 items), and attention- seeking(4items), and self-centered behavior(5items) scales responding according to 5- Likert scale ranging from (always- never). The results showed that the level of selfie- liking is high among the research sample, and that there are significant differences in selfie- liking, due to the gender, with high level for females., and that there is high correlation between the two variables. After conducting a regression analysis, it was found that the narcissistic personality trait and self-centered behavior made the greatest contribution to the selfie- liking among Baghdad University students.